The Preliminary Results of the Chemical-radiological Investigations of the Soils on the Territory of the Makhata Mountain - Matiashvili, Sophiko B. (Journals of Georgian Geophysical Society, 2017)
A detailed environmental study of any section of the city of Tbilisi on the subject of environmental hazards is a particularly urgent issue. From this point of view, the area of ​​Mount Mahat is special, because Here for several years now operates the Church of Virgin Mary of Iberia Cathedral. 2012-13 years. A radioecological and agrochemical study was conducted on that site in the territory of Mount Makhata, where the Church of the Iberian Mother of God will be located. Laboratory studies of soil samples taken from this area were carried out at the research center of the Ministry of Agriculture. According to the initial data of environmental monitoring, it can be considered that the investigated territory is either a polluted medium level or a little polluted. Here the criterion is the content of a specific pollutant element, which should be less than the maximum permissible concentration of radionuclide in excess of the former Soviet standards. The background of agrochemical contamination on the investigated site is also not alarming. However, in spite of the fact that the radiation monitoring did not reveal significant contamination with radiation spots or point sources, periodic ecological monitoring of the investigated territory should continue to be continued in the future.